Pemanfaatan Kecerdasan Buatan (Artificial Intelligence) Dalam Pengembangan Model Bisnis Digital Berkelanjutan - Taufiqa Widya; Zahra Nurafifah (CV. SINAR HOWUHOWU, 2026)
The rapid development of digital technology has significantly transformed the way organizations create, deliver, and sustain business value. One of the key technologies driving this transformation is Artificial Intelligence (AI). This study aims to analyze the utilization of AI in the development of sustainable digital business models and to identify its benefits and implementation challenges. The research employs a qualitative approach using a literature review method based on scientific journals, books, research reports, and relevant academic publications. Data were analyzed through content analysis to identify major themes related to AI, digital business models, and business sustainability. The findings indicate that AI contributes to improving operational efficiency, supporting data-driven decision-making, fostering product and service innovation, and enhancing customer relationships through personalized services. Furthermore, AI supports business sustainability by optimizing resource utilization, reducing waste, and improving supply chain efficiency. However, AI implementation still faces several challenges, including data privacy concerns, information security issues, algorithm transparency, and human resource readiness. Therefore, appropriate implementation strategies are required to maximize the benefits of AI in supporting innovative, competitive, and sustainable digital business models.